Hûthiyya as a sect of Zaidiyya: Ideological Foundations and Pedagogical Peculiarities - Ahmed Muhammed Ed-dağşî (İslami İlimler Dergisi)
This article aims at enlightening the ideological foundations and pedagogical peculiarities of al-Hûthiyya which is one of the groups of Shia, Zaidiyya, an effective sect in Yemen. In this article, there has been given informations about the establishment and process of being an organization of al-Hûthiyya, founded at the end of 1990’s by Badr al-Dîn al-Hûthî. It is dealt with the movement’s armed fight as a new stage for them after 2004. In the end of the article, the findings about al-Huthiyya has been summarized and given some advices for the solution.